International migrations and the reorganization of care. The cases of THE Republic of Moldova, Romania and Ukraine - Alice Vianello, Francesca (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
Since the relevance of migrations from Eastern Europe to Southern Europe, this paper presents a qualitative study carried out in Moldova, Romania and Ukraine concerning the reorganization of care to address the impact of care drain. In particular the reorganization of care for children and elderly left behind is analised, taking into account the four poles of the «care diamond»: transnational families, the State, the third sector and the market. The perspective from the countries of origin, the comparison between two systems of care, for childern and for elderly people, and the inclusion of State and civil society into the analysis of care provisions provide a more complete picture of the social transformations generated by mass emigration.